Various Approaches in Islamic Religious Education Curriculum Development - Effendi, Silma Mazia (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
The curriculum encompasses learning plans in schools or conferences, with a modern interpretation emphasizing a holistic understanding of objectives, teaching methods, and content. However, challenges related to the alignment of the Islamic Religious Education (PAI) curriculum with modern demands necessitate continuous efforts to adapt to the evolving times, integrate technology, and ensure the curriculum's relevance and quality. The role of the PAI curriculum in Indonesia is to guide behavior and commercial activities in line with Islamic values, fostering harmony among people of different faiths. The curriculum should reflect the moral and religious values of Islam, and its implementation involves teachers shaping understanding, beliefs, and appreciation of these values. The development of the PAI curriculum aligns with the concept of shaping a perfect human (al-Kamil) according to Islamic teachings. To achieve this goal, collaboration among educators, stakeholders, and the government is crucial to enhance and maintain the quality of Islamic curricula in Indonesia to remain relevant and effective